2009
DOI: 10.1590/s1678-77572009000700020
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of ART: improving on success through further research

Abstract: Since the introduction of the Atraumatic Restorative Treatment (ART) approach over twenty years ago, more than 190 research publications have appeared. The last research agenda defining research priorities for ART was published in 1999. The objective of the present work was to review existing research in the context of future research priorities for ART. Material and Methods: An internet survey was conducted amongst those who had published on ART or were known to be working on the ART approach, to solicit thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…All 1 st authors of published papers on ART, with workable email addresses, were approached and were asked what they considered to be the future research priorities for ART. The findings have been reported by Holmgren and Figueiredo 12 (2010). By the 1 st of December 2009, Pubmed contained 178 published articles on ART, of which 172 are related to the Atraumatic Restorative Treatment approach.…”
Section: Highlights: Research Agenda For Artsupporting
confidence: 88%
“…All 1 st authors of published papers on ART, with workable email addresses, were approached and were asked what they considered to be the future research priorities for ART. The findings have been reported by Holmgren and Figueiredo 12 (2010). By the 1 st of December 2009, Pubmed contained 178 published articles on ART, of which 172 are related to the Atraumatic Restorative Treatment approach.…”
Section: Highlights: Research Agenda For Artsupporting
confidence: 88%
“…Of these consequences, the latter is especially apparent with regard to glass-ionomer cement (GIC)-based fissure sealants [20], despite the fact that systematic reviews have found no difference between the caries-preventive effect of GIC and that of resin-based sealants [26, 27]. For these reasons, it has been repeatedly argued that: (i) biological outcomes should take precedence over mechanical ones; (ii) because sealants are placed in pits and fissures in order to prevent the onset of caries manifestation or to arrest it, the true outcome of such intervention should therefore be expressed in terms of how well such intervention has managed to achieve this objective [35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a well-accepted dental caries management approach in children 2 , 10 , the Atraumatic Restorative Treatment (ART) has been recommended as a possible treatment protocol for use amongst people with disabilities 12 , 17 . It was thought that ART could overcome some of the problems mentioned above in treating people with disabilities, because it only uses hand instruments, which are not noisy.…”
Section: Introductionmentioning
confidence: 99%